With peppermints you’re not my prince: Aroma modulates self-other integration - Sellaro, Roberta (Atten Percept Psychophys, 2015)
Recent studies showed that self-other integration, as indexed by the joint Simon effect (JSE), can be modulated by biasing participants towards particular (integrative vs. exclusive) cognitive-control states. Interestingly, there is evidence suggesting that such control states can be induced by particular odors: stimulating odors (e.g., peppermint aroma) seem to induce a more focused, exclusive state; relaxing odors (e.g., lavender aroma) are thought to induce a broader, more integrative state. In the present study, we tested the possible impact of peppermint and lavender aromas on self-other integration. Pairs of participants performed the joint Simon task in an either peppermint- or lavender-scented testing room. Results showed that both aromas modulated the size of the JSE, although they had a dissociable effect on reaction times (RTs) and percentage of errors (PEs). Whilst the JSE in RTs was found to be less pronounced in the peppermint group, compared to the lavender and no-aroma groups, the JSE in PEs was significantly more pronounced in the lavender group, compared to the peppermint and no-aroma group. These results are consistent with the emerging literature suggesting that the degree of self-other integration does not reflect a trait but a particular cognitive state, which can be biased towards excluding or integrating the other in one’s self-representation.